Exploring the deadlift - Bird, S. (Strength and Conditioning Journal, 2010)
THE DEAD LIFT (DL) AND ITS VARIATIONS ARE WIDELY ACCEPTED BY STRENGTH AND CONDITIONING COACHES AS ONE OF THE "BIG 3" EXERCISES PRESCRIBED TO DEVELOP "TOTAL BODY STRENGTH," SPECIFICALLY THE HIP AND KNEE EXTENSORS, SPINAL ERECTORS, QUADRATUS LUMBORUM, CORE ABDOMINAL MUSCULATURE, AND BACK AND FOREARM MUSCLES. THEREFORE, THE PURPOSE OF THIS COLUMN IS TO INTRODUCE STRENGTH AND CONDITIONING COACHES TO THE MANY SPORT-SPECIFIC APPLICATIONS FOR COMMON DL VARIATIONS USED IN STRENGTH TRAINING PROGRAM DESIGN, WITH SPECIFIC EMPHASIS ON THE ROMANIAN DL, FOR ITS POTENTIAL USE IN THE TEACHING PROGRESSION OF THE POWER CLEAN.